2022
DOI: 10.3390/molecules27165308
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Optical Properties of ZnO:Ce Nano Film

Abstract: ZnO and cerium-doped ZnO on a glass substrate have been prepared by the sol–gel method using the spin coating technique and water bath growth process. Ce-doping concentration on film structure, morphology, and optical properties is investigated. The result indicated that the hexagonal wurtzite ZnO with high crystalline quality formed on the substrate. The crystal parameters a and c decreased, crystal size increased, and the compressive strain formed after Ce-doping. Formed un-, 3%, 6%, 12% Ce-doped ZnO film ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The average crystal size of 1% Ce/ZnO (90 nm) was smaller compared to pure ZnO, which was 117 nm. This finding is in agreement with other findings reported elsewhere [24,26,27]. Ce-O-Zn bonds formed on the surface of Ce-doped ZnO samples limit or restrain the crystallites' growth, causing a decrease in crystallite size [28].…”
Section: Xrd Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The average crystal size of 1% Ce/ZnO (90 nm) was smaller compared to pure ZnO, which was 117 nm. This finding is in agreement with other findings reported elsewhere [24,26,27]. Ce-O-Zn bonds formed on the surface of Ce-doped ZnO samples limit or restrain the crystallites' growth, causing a decrease in crystallite size [28].…”
Section: Xrd Analysissupporting
confidence: 93%
“…However, due to the contribution of CeO 2 to the diminished ZnO peak (Figure 3b), collecting ZnO diffraction data becomes challenging. Correspondingly, the crystallite size, D, is obtained by employing the Debye-Scherrer formula [24].…”
Section: Xrd Analysismentioning
confidence: 99%
“…Some industries, such as paper, textiles, leather, cotton, and rubber, directly discharge toxic dyes into water bodies . Rhodamine blue (RhB) and methylene blue (MB) are widely used cationic dyes (basic dyes) . MB, a blue-colored dye, has an aromatic molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Rhodamine blue (RhB) and methylene blue (MB) are widely used cationic dyes (basic dyes). 3 MB, a blue-colored dye, has an aromatic molecular structure. A contaminated dye with an aromatic structure such as MB will introduce toxicity to marine life and be incorporated in humans by the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Xin et al reported diminished optical transmittance in visible range and increase in bandgap energy with increment in Ce-doping content. The intense blue emission with a color purity revealed potential applications of Ce-ZnO films as a suitable material for development of near ultraviolet LED and blue light source [47].…”
Section: Introductionmentioning
confidence: 99%